The History of the Struggle between Rationalism and Traditionalism in Islamic Thought: A Study of the Dialectic of the Mu'tazilah and Ahl al-Sunnah - Abdul Rahman; Muhammad Sopyan; Khairuddin Hasibuan (ISNU Nine-Star Multidisciplinary Journal, 2026)
The history of Islamic thought demonstrates an intellectual dynamic characterized by debates between rationalism and traditionalism in understanding religious teachings. One of the most significant forms of this struggle is the dialectic between the Mu'tazilah, who emphasized the role of reason in interpreting revelation, and the Ahl al-Sunnah, who placed the authority of the revealed text as the primary foundation of Islamic theology. This study aims to analyze the historical background of the emergence of Mu'tazilah rationalism, its theological principles, and the Sunni theological responses formulated by Abu al-Hasan al-Ash'ari and Abu Mansur al-Maturidi in the context of the development of Islamic thought. This study uses a qualitative method with a historical approach and analysis of the thoughts of figures through a bibliography of classical and modern literature in the field of Islamic theology. The results show that the emergence of the Mu'tazilah was not only influenced by internal theological debates among Muslims, but also by political dynamics and intellectual developments during the Abbasid period that opened up space for interaction with philosophical traditions. The principles of Mu'tazilite rationalism formulated in al-Uṣūl al-Khamsah emphasize the importance of reason in understanding God's oneness and justice, while the Ahl al-Sunnah response seeks to balance rationality with the authority of revelation through a more moderate theological formulation. The dialectic between these two schools of thought ultimately made a significant contribution to the development of theology and the formation of the Islamic intellectual tradition. Therefore, a study of this intellectual struggle can serve as a reflective foundation for understanding the relationship between revelation and rationality in the development of Islamic thought, while also opening up a space for dialogue for the development of Islamic theological studies in the contemporary era.